Inclusivity in Islamic Conservatism: The Moderate Salafi Movement in Kediri, Indonesia - Qomarul Huda, Muhammad; Sulaeman, Mubaidi; Marpuah, Siti (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2023)
This article analyzes the moderate Salafi movement in Kediri through a case study of Jemaah Hijrah at Imam Muslim Islamic Boarding School. This research aims to reveal the characteristics, approaches, and development of religious understanding carried out by Jemaah Hijrah in the context of the moderate Salafi movement in Indonesia. The research method used is a qualitative approach. Data were collected through in-depth interviews with Jemaah Hijrah congregation and Imam Muslim Islamic Boarding School administrators, participatory observation during religious activities, and document analysis related to the views and principles adopted by Jemaah Hijrah. The results showed that the Jemaah Hijrah there adheres to a moderate Salafi approach, emphasizing being inclusive and tolerant of variations in interpretations of Islam. They seek to maintain core Salafi values while remaining open to dissent on religious issues. The movement's sustainability depends on an educational approach that provides space for discussion and dialogue rather than a rigid emphasis on a single interpretation and avoids actions that breed blind fanaticism, where blind fanaticism is the root of all hostility and division. This research provides insights into how the moderate Salafi movement can thrive in local settings and how this inclusive approach balances religious conservatism and acceptance of difference. The findings contribute to the understanding of the broader community that the development of the Salafi movement in Indonesia is not monolithic but varies and adapts according to local situations and the demands of the times.